The association between objective and subjective socioeconomic status and subjective well-being: A meta-analytic review - Tan, Jacinth J X; Kraus, Michael W; Carpenter, Nichelle C; Adler, Nancy E (Psychological bulletin, 2020)
This meta-analysis tested if the links between socioeconomic status (SES) and subjective well-being (SWB) differ by whether SES is assessed objectively or subjectively. The associations between measures of objective SES (i.e., income and educational attainment), subjective SES (i.e., the MacArthur ladder SES and perceived SES), and SWB (i.e., happiness and life satisfaction) were synthesized across 357 studies, totaling 2,352,095 participants. Overall, the objective SES and subjective SES measures were moderately associated (r = .32). The subjective SES-SWB association (r = .22) was larger than the objective SES-SWB association (r = .16). The income-SWB association (r = .23) was comparable with the ladder SES-SWB association (r = .22) but larger than the perceived SES-SWB association (r = .196). The education-SWB association (r = .12) was smaller than the associations with both measures of subjective SES. The subjective SES-SWB association was partially explained by common method variance. The subjective SES-SWB association, particularly with the ladder SES measure, also mediated the objective SES-SWB association. In moderation analyses, the objective SES-SWB associations strengthened as samples increased in wealth and population density. The subjective SES-SWB associations strengthened as samples increased in population density, decreased in income inequality, and decreased in relative social mobility. The role of common method variance, social comparisons, and other processes in explaining the SES-SWB links are discussed. (PsycInfo Database Record (c) 2020 APA, all rights reserved).